The practice and perception of precautionary allergen labelling by the Australasian food manufacturing industry. Issue 7 (10th April 2017) - Zurzolo, G. A.; Peters, R. L.; Koplin, J. J.; de Courten, M.; Mathai, M. L.; Tye‐Din, J. A.; Tang, M. L. K.; Campbell, D. E.; Ponsonby, A‐L.; Prescott, S. L.; Gurrin, L.; Dharmage, S.C.; et al.
Summary: Background: The precautionary allergen labelling (PAL) and Voluntary Incidental Trace Allergen Labelling (VITAL ® ) tools were designed by industry to assist consumers with selecting safe foods for consumption. However, a sizeable proportion of food products bear no label, and it is unclear whether these products are free from allergens and therefore safe to consume or have simply not undergone a risk assessment and therefore remain unlabelled for that reason. Objective: To assess the prevalence of unlabelled products that have undergone a risk assessment process and to examine the factors influencing industry's uptake of the VITAL ® process. Methods: A web‐based questionnaire was distributed to Australasian food and grocery manufacturers. Results: One hundred and thirty‐seven Australasian manufacturers were contacted, and 59 questionnaires were returned (response rate: 43%). The respondents represented 454 different manufacturing sites. Manufacturers reported that 23% (95% CI 19‐28) of products (n=102/434) that had been through the VITAL ® risk assessment process had no PAL statement on the label. 34% (95% CI 30‐38), (n=204/600) of products that had undergone another (non‐VITAL ® ) risk assessment process had no PAL statement. In examining the factors that influenced industry's uptake of the VITAL ® process, 25 manufacturers reported on factors that influenced the uptake of the VITAL ® process, 76% (CI 95% 55‐91) reported that VITAL ® was an effective tool because it was based on science; 52% (CI 95% 31‐72) reported that it was too time‐consuming and 36% (CI 95% 18‐57) identified a concern with it not being endorsed by the government. Conclusion and Clinical Relevance: Currently, we estimate that at least 30% of products may have been through a risk assessment process and yet bear no PAL statement on the label. Permissive labelling could be incorporated onto these products if they have been assessed to be safe for consumption.